Urban particulate matter stimulation of human dendritic cells enhances priming of naive CD8 T lymphocytes. Issue 4 (28th November 2017) - Pfeffer, Paul E.; Ho, Tzer R.; Mann, Elizabeth H.; Kelly, Frank J.; Sehlstedt, Maria; Pourazar, Jamshid; Dove, Rosamund E.; Sandstrom, Thomas; Mudway, Ian S.; Hawrylowicz, Catherine M.
Summary: Epidemiological studies have consistently shown associations between elevated concentrations of urban particulate matter (UPM) air pollution and exacerbations of asthma and chronic obstructive pulmonary disease, which are both associated with viral respiratory infections. The effects of UPM on dendritic cell (DC) ‐stimulated CD4 T lymphocytes have been investigated previously, but little work has focused on CD8 T‐lymphocyte responses despite their importance in anti‐viral immunity. To address this, we examined the effects of UPM on DC‐stimulated naive CD8 T‐cell responses. Expression of the maturation/activation markers CD83, CCR7, CD40 and MHC class I on human myeloid DCs (mDCs) was characterized by flow cytometry after stimulation with UPM in vitro in the presence/absence of granulocyte–macrophage colony‐stimulating factor (GM‐CSF). The capacity of these mDCs to stimulate naive CD8 T‐lymphocyte responses in allogeneic co‐culture was then assessed by measuring T‐cell cytokine secretion using cytometric bead array, and proliferation and frequency of interferon‐ γ (IFN‐ γ )‐producing T lymphocytes by flow cytometry. Treatment of mDCs with UPM increased expression of CD83 and CCR7, but not MHC class I. In allogeneic co‐cultures, UPM treatment of mDCs enhanced CD8 T‐cell proliferation and the frequency of IFN‐ γ + cells. The secretion of tumour necrosis factor‐ α, interleukin‐13, Granzyme A and Granzyme B were also increased. GM‐CSF alone, and in concert with UPM, enhanced many of these T‐cell functions. The PM‐induced increase in Granzyme A was confirmed in a human experimental diesel exposure study. These data demonstrate that UPM treatment of mDCs enhances priming of naive CD8 T lymphocytes and increases production of pro‐inflammatory cytokines. Such UPM‐induced stimulation of CD8 cells may potentiate T‐lymphocyte cytotoxic responses upon concurrent airway infection, increasing bystander damage to the airways. Abstract : Urban particulate matter (UPM) air pollution is associated with exacerbations of chronic airway diseases and also with respiratory tract infections. Using in vitro cultures we show that UPM treatment of human myeloid dendritic cells enhances priming of naive CD8 T lymphocytes and increases the production of pro‐inflammatory cytokines such as interferon‐ γ and Granzymes.